Project delay: key electrical construction factors in Hong Kong - Chiu, Betty W. Y.; Lai, Joseph H. K. (Journal of Civil Engineering and Management, 2017)
The price of construction project delays is too substantial to pay. Electrical construction is a critical activity influencing project completion, but research on its delay factors was limited. Aimed at contributing knowledge to this niche area, a study was conducted in Hong Kong. 56 delay factors, in 10 groups, were found with electrical construction. Processing the data of a survey on 64 consultants and 68 contractors revealed “insufficient labour”, “late decision making of client” and “insufficient electrical contractor” as the top delay factors. Strong agreements on the importance rankings of the delay factors existed between the consultant and contractor groups, and the principal factor components were “incompetent project team members”, “lack of skillful labour” and “poor on-site planning”. Besides discussing the common problems underlying the delay factors, recommendations were made for avoiding the problems. An understanding of the delay factors would help construction stakeholders in taking proactive measures to prevent project delay. The approach of the study can serve as reference for similar, future research in construction management.